Assessing the Antecedents of Ready-to-Eat (RTE) Food Purchase Intention of Urban Students - Intisar Alam, Muhammad; Jim, Mahafizur Rahman; Bari Chowdhuri, Abu Sayef Md Muntaquimul (Jahangirnagar University Journal of Management Research, 2024)
The aim of this study is to determine the factors influencing Bangladeshi university students’ intentions to purchase ready-to-eat food. 320 people took part in the study, and information was gathered using an organized questionnaire through an online survey on Facebook, a social networking site. The multiple regression model has been used to analyze the data. Eight predictors are considered to develop the research hypotheses. By using the multiple regression model, it is found that university students consider availability of the product, preparation and time convenience, taste, health consciousness, cost-effectiveness of the food in shaping their RTE food purchase intention. Additionally, lifestyle pressure and brand image are found insignificant towards behavioral intention. This study provides managerial and theoretical contributions by focusing the scope on university students and determining the relationship with purchase intention of RTE foods. Moreover, the conceptual model is a new theoretical attribution with existing literature which opens new opportunities for future avenues. Ultimately, the constraints and prospects for further investigation have been deliberated.